CONTINUOUS GLUCOSE MONITORING AS AN INNOVATIVE DIGITAL HEALTH TECHNOLOGY IN TYPE 1 DIABETES: PSYCHOSOCIAL BARRIERS, PHYSICAL ACTIVITY AND EQUITY OF ACCESS - Aleksander Krupski; Michał Marusza; Victoria Stielow; Antonina Zatyka (International Journal of Innovative Technologies in Social Science, 2026)
Research objectives. While CGM plays an essential role in managing the modern type one diabetic's condition it becomes most critical for those with type 1 diabetes who engage in physical activity as they are often fearful of experiencing low blood glucose levels (hypoglycemia) or post-exercise elevated glycemic levels (dysglycemia), which can limit their ability to participate in such activities. To conduct a focused evaluation of the recent evidence-based research regarding the psychosocial and access related aspects of using Continuous Glucose Monitoring (CGM) technology among physically active individuals with type 1 diabetes. Methods. Using a focused search strategy that included articles from peer-reviewed journals indexed within MEDLINE/PubMed published between 2022 and 2026 this article has reviewed the original evidence-based research. Key findings. There is strong evidence concerning exercise related safety, the immediate nature of clinical decision making and fear of experiencing low blood glucose (hypoglycaemia) when exercising. Alerts for predictive post-exercise hypoglycaemic events and the use of CGM that includes information on exercise can both potentially be effective at reducing episodes of clinically significant post-exercise hypoglycaemia. Generic quality of life and diabetes distress have very little direct evidence available regarding these as outcomes in physically active populations. Conclusions. CGM provides meaningful clinical support for safer exercise in type 1 diabetes. However, it is insufficient to overcome behavioural barriers by itself. Inequitable access to CGM represents a major barrier to achieving its potential benefit in the "real world".